Virtual society? : technology, cyberbole, reality - Woolgar, Steve (Oxford University Press, 2002)
Almost all aspects of social, cultural, economic and political life stand to be affected by the new electronic technologies. Virtual Society? is one vision of the consequential impact of these technologies. But to what extent and in what ways are the Internet and other electronic technologies really changing our lives? To what extent are we moving to a 'virtual society'? This collection provides a comprehensive set of detailed empirical studies of the genesis and use of these new technologies, ranging widely across application areas: from cyber-cafés to new media; email and organizational memory: to surveillance-capable technologies in the workplace; virtual reality to CCTV in high-rise housing; stock exchange addicts to student study networks. It offers a unique perspective -- analytic scepticism -- for making sense of some surprisingly counterintuitive results, and for developing a refreshingly critical view of many taken-for-granted assumptions about the impact of the Internet on social relations and institutions. Each chapter presents a high quality exemplar of its own disciplinary perspective, addressed to a general social science audience. The diversity of disciplinary perspectives is brought to bear in a central message laid out in the opening discussion of the 'Five Rules of Virtuality', that with due reflexive caution and ironic sensitivity, general messages can be drawn from the observations of particular substantive contexts. In particular, claims that we are moving to a 'virtual society' need to be tempered by a reassessment of connections between what counts as 'real' and 'virtual'. --Publisher description.